Hubungan pengetahuan ibu tentang MPASI dan Jenis kelamin balita dengan kejadian Stunting - Iin Setiawati (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: Based on the Indonesian Toddler Nutrition Status Survey (SSGBI), the number of stunting is 38%, this figure is second highest number in East Java. This survey was conducted at 33 special locations (locuses) in Bangkalan, involving 300 samples and the results were 38% experienced stunting. Objective: This study aims to analyze the relationship between mother's knowledge about complementary foods and the sex of toddlers with the incidence of stunting. Methods: analytic research method with a cross-sectional approach, independent variable is mother's knowledge of complementary foods and the sex of toddlers, dependent variable is stunting. The research sample was 30 toddlers. Univariate test using frequency distribution table and bivariate test with regression 0.05 Results: Most of the knowledge of mothers about complementary foods is 66.7%, statistical test shows 0.141 > 0.05 (ρ>α) meaning that there is no relationship between mother's knowledge about complementary foods and the incidence of stunting. Most of the sexes of toddlers are male, namely 60%, statistical test shows 0.014<0.05 (ρ<α) meaning that there is a relationship between the sex of toddlers and the incidence of stunting. Conclusion: Mother's knowledge about complementary foods has no relationship with stunting, the gender of toddlers has a relationship with stunting.